Ефективний потенцiал мiжелектронної взаємодiї для напiвобмеженого електронного газу з врахуванням поправки на локальне поле - Markovych, B. M.; Zadvorniak, I. M. (Publishing house "Academperiodika", 2018)
The effective potential of electron–electron interaction and the two-particle “density–density” correlation function have been calculated for a simple semiinfinite metal making allowance for the local-field correction. The influences of a flat interface and various models of local-field correction on the results of calculations are analyzed.